Gagasan K.H Wahab Chasbullah tentang Pencak Silat di Pondok Pesantren Bahrul Ulum Tambakberas Jombang (1967-1971) - Muslimin, Zakiyah Darodjat Cahya; Afiyanto, Hendra (SHAHIH: Journal of Islamicate Multidisciplinary, 2021)
This study was conducted to find out KH Wahab Chasbullah's idea of pencak silat at the Bahrul Ulum Tambakberas Islamic Boarding School, Jombang. Using historical research methods, this study finds that the basic idea of KH Wahab Chasbullah in developing pencak silat in the pesantren environment is to preserve the nation's cultural heritage and cultivate the spirituality of the santri. Through his idea, KH Wahab Chasbullah divided pencak silat into physical and non-physical aspects. Another finding of this research is that the activities of Pencak Silat are carried out to instill love for the Indonesian nation. Pencak silat in the Bahrul Ulum Tambakberas Islamic Boarding School in Jombang has three important functions, namely the function of self-defense, the function of art and the function of religion. This study complements the study of Islamic moderation, Islamic negotiations on local culture, and the contribution of Islamic boarding schools to achieving independence.